Analisis Pelaksanaan Pendidikan Antikorupsi Siswa Melalui Penanaman Nilai Islam SD Muhammadiyah Noyokerten - Finka Arya Juwita; Suyitno Suyitno; Bianca Ayu Prastika; Risky Dwi Cahya (Universitas Negeri Padang, 2023)
Anti-corruption education should be instilled from an early age starting from the primary school level, and implemented through subjects either outside or inside the classroom. Teachers must have the right strategies in place to instill anti-corruption education. So this research must be researched to instill the values of anti-corruption education in elementary schools. The purpose of this study is to determine how teachers implement strategies in growing anti-corruption education. This research uses qualitative research with a case study approach. The samples in this study were principals, teachers, and students at SD Muhammadiyah Noyokereten Yogyakarta. Data collection techniques use structured interviews and documentation. The research results obtained strategies implemented by integrating Islamic values in learning activities through learning objectives, materials, processes, and evaluations. The supporting factors and obstacles are conducive environmental conditions, supportive facilities and facilities such as meals prepared by the school, and school programs through the reflection of students and factors from inside and outside. This research implies that all school stakeholders can realize the importance of instilling anti-corruption values early to change honest generations and responsibilities in the future.